El consumo de noticias en Facebook y Twitter en estudiantes de comunicación durante la pandemia de la COVID-19 - Merino Navarro, Cynthia del Pilar (2021)
With the constant information disseminated by different media about Covid-19, communication students have found it necessary to increase their consumption of news to try to stay informed as well as possible, relying on Facebook and Twitter. This work clarifies the preferences of media and news topics, proposing a consumption profile of the students at the University of Lima and the Pontifical Catholic University, analyzes their preference for social networks and the level of influence of this news on them. This study was carried out on 25 communication students from the University of Lima and Pontificia Universidad Católica del Perú, through online focus groups. The analysis concludes that there is an inclination towards social networks and a departure from traditional ones mainly due to the way they present the news and the facilities that social networks offer them. The consumer profile at the University of Lima reflects a critical and analytical interest, while at the PUCP it is an interest in social and humanitarian issues. Finally, the influence of the news on them and their actions depends on the level of identification they have with what they have read, going from clicking the like button to taking actions to the streets.